INTERPRETASI CITRA RADAR (RADIO DETECTION AND RANGING) DOPPLER BMKG (BADAN METEOROLOGI KLIMATOLOGI DAN GEOFISIKA) PEKANBARU DALAM MEMPREDIKSI CURAH HUJAN DI KOTA PEKANBARU - Aprianti, Dini; Ardhitama, Arysthya; Fitri, Yulia (Sistem Informasi, 2015)
In a study of Indonesia is located in the geographic equator. Because of the location of Indonesia became the countrys tropical climate, which is marked with rainfall almost throughout the year occur with a high enough intensity. The negative impact of high rainfall that flooded, because the volume of water will overflow and uncontrolled. To measure the amount of rainfall in an area used rain gauges infernal surface manual and automatic. However, rain gauges and automatic manual still has the disadvantage that it can not predict what happens next. Radar imagery is one of the modern gauges and able to provide more accurate data. The radar also can detect the intensity of rainfall in bad weather conditions such as rain storms, floods, tornadoes and lightning. So from the description above, rainfall predictions will be verified from the results of the Doppler radar image interpretation with rain gauges located in Pekanbaru BMKG based on observational data were analyzed with a test statiskit MAE test, degree of homogeneity, and the value of the correlation coefficient. Based on the test results Statistics. Such as: MAE test, Correlation Coefficient and Homogeneity Test, the radar is able to predict the rainfall in Pekanbaru correctly.